DOI: 10.14264/88a04bb
|View full text |Cite
|
Sign up to set email alerts
|

UQ eSpace

Abstract: Simulation which incorporates numerical method is practical in investigating the effect of ultrasonic excitations on the acoustic pressure and flow patterns of fluid with arbitrary settings as it can produce reliable results in a relatively short time even for complex cases. This thesis aims to develop efficient simulation of acoustic pressure field generated by ultrasonic transducer using ANSYS Workbench to obtain accurate data of the resulting flow and pressure fields for harmonic ultrasonic excitations. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Of course, the main compounds of the plant are flavonoids (subdivided to flavones, flavonols, flavanones and flavanonols, flavanols and the polymers of flavanols), triterpenoids, steroids, monoterpenoids and sesquiterpenoids, lignans, organic acids, nitrogen-containing compounds, hydroxycinnamic acids and other compounds. [41][42][43][44] This antioxidant content caused to use of phytochemicals and potent natural antioxidant phenolics in the plant extracts as an appropriate source of suitable bio reducers to green synthesis of nanoparticles. [26] Therefore, the presence of various types of antioxidant phenolics especially in the family of flavonoids nominated the plant as the best source of bioreducing agents to biosynthesis of nanostructures during this study.…”
Section: Preparation and Characterization Of The Cu/ni/rgomentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, the main compounds of the plant are flavonoids (subdivided to flavones, flavonols, flavanones and flavanonols, flavanols and the polymers of flavanols), triterpenoids, steroids, monoterpenoids and sesquiterpenoids, lignans, organic acids, nitrogen-containing compounds, hydroxycinnamic acids and other compounds. [41][42][43][44] This antioxidant content caused to use of phytochemicals and potent natural antioxidant phenolics in the plant extracts as an appropriate source of suitable bio reducers to green synthesis of nanoparticles. [26] Therefore, the presence of various types of antioxidant phenolics especially in the family of flavonoids nominated the plant as the best source of bioreducing agents to biosynthesis of nanostructures during this study.…”
Section: Preparation and Characterization Of The Cu/ni/rgomentioning
confidence: 99%
“…[40] More than 280 species of the genus hawthorn have been described and some literatures showed that hawthorn species includes 150 to 1200 species. [41][42][43][44] In fact, they are native to Northern temperate zones, mostly between latitudes 30°and 50°N and comprises of a complex group of trees and shrubs. The average height of hawthorn trees is between 2 to 5 m and even normal size trees can reach a height of up to 10 m. Leaves of the most species have two leafy bracts, they are 1.5 to 5 cm long, glabrous, broad-ovate or obovate and have serrated margins with three to seven lobes.…”
Section: Introductionmentioning
confidence: 99%